Walking or breathing: comparing the 6-minute walking distance test to the pulmonary function test for lung resection candidates - Ali Mehri; Fariba Zabihi; Taha Sharafian; Mona Kabiri; Reza Rezaei (Journal of Cardiovascular and Thoracic Research)
Introduction: Given the limited use of the 6-minute walking distance (6MWD) test as a replacement for standard tests in thoracic surgery, insufficient research exists on the prognostic value of this test, and further studies are necessary. This study aimed to investigate the correlation between pulmonary function tests (PFT) and the 6MWD test in lung resection patients. Methods: This cross-sectional study, conducted in 2021-2022, involved lung resection candidates referred to the thoracic surgery clinic. Demographic data, including age, sex, and body mass index (BMI), were collected, and pulmonary function tests and 6MWD tests were conducted for all patients. The sample size of the study was 31, and all patients received routine treatment during hospitalization. Results: Of the 31 subjects included in the study, 16 were male (51.6%) and 15 (48.4%) were female. The mean age of the patients was 33.45±13.78 years. The median forced expiratory volume in one second (FEV1) and the mean ratio of FEV1/forced vital capacity (FVC) were 2.16 (1.49–2.85) liters and 81.80±7.34%, respectively. No significant correlation was found between the results of 6MWD and PFT, including FVC, FEV1, and FEV1/FVC ratio (P>0.05). Conclusion: The 6MWD test is a more economical and easily accessible test than PFT. However, this study found no correlation between the 6MWD test and spirometry parameters. Therefore, we suggest that surgeons should not rely on the 6MWD test as a predictive value for assessing respiratory function in lung resection candidates. The study’s findings have important implications for clinical practice.